Zika Virus-Mediated Death of Hippocampal Neurons Is Independent From Maturation State - Büttner, Caroline; Heer, Maxi; Traichel, Jasmin; Schwemmle, Martin; Heimrich, Bernd (Frontiers in Cellular Neuroscience, 2019)
Zika virus (ZIKV) infection of pregnant women and diaplazental transmission to the fetus is linked to the congenital syndrome of microcephaly in newborns. This neuropathology is believed to result from significant death of neuronal progenitor cells. Here we examined the fate of neurons in the developing hippocampus, a brain structure which houses neuronal populations of different maturation states. For this purpose, we infected hippocampal slice cultures from immunocompetent newborn mice with ZIKV and monitored changes in hippocampal architecture. In neurons of all hippocampal subfields ZIKV was detected by immunofluorescence labeling and electron microscopy. This includes pyramidal neurons that maturate during the embryonic phase. In the dentate gyrus, ZIKV could be found in the Cajal-Retzius cells which belong to the earliest born cortical neurons, but also in granule cells that are predominantly generated postnatally. Intriguingly, virus particles were also present in the correctly outgrowing mossy fiber axons of juvenile granule cells, suggesting that viral infection does not impair region- and layer-specific formation of this projection. ZIKV infection of hippocampal tissue was accompanied by both a profound astrocyte indicating tissue injury and a microglia response suggesting phagocytotic activity.Furthermore, depending on the viral load and incubation time, we observed extensive overall neuronal loss in the cultured hippocampal slice cultures. Thus, we conclude ZIKV can replicate in various neuronal populations and trigger neuronal death independent of the maturation state of infected cells.